Childhood depression in children (0-5 years) and its impact n psychomotor development (Cuestiones de Fisioterapia, 2000)
The Un specificity of the infant depressive descriptions which are showed into a hidden and latent form, in 90% of the cases (Citrin and McNew, 1968), the frequency in comorbidity situations, that blur the limits of several child's disturbances and that affect to the psychomotor development, especially in child's sensorimotor stage (0-18 months, by Piaget) (Shaffi, 1997), is the objective of this study, in which it's described the expressive variability of these ones and their repercussion into different areas of development.